PENGARUH MOTIVASI KERJA DALAM MEMEDIASI PENGARUH PENGEMBANGAN KARIR TERHADAP KINERJA - Natalia, Ni Komang Sisi Sania; Netra, I Gusti Salit Ketut (E-Jurnal Manajemen; Vol 9 No 4 (2020)DO - 10.24843/EJMUNUD.2020.v09.i04.p14, 2020)
This study aims to determine the role of work motivation in mediating the effect of career development on employee performance. This research was conducted at the Single Fin Surf Shop, Cafe and Bar Badung Regency. The number of samples taken was 106 employees, using the saturated sample method. Data collection was obtained from the results of questionnaires. Data analysis, path analysis, single analysis and VAF analysis. The results of this study found that career development had a positive and significant effect on employee work motivation. Career development has a positive and significant effect on employee performance. Work motivation has a positive and significant effect in mediating the influence between career development on employee performance. Bad Fin Single Shop, Cafe and Bar Badung Regency should provide career opportunities related to education to carry out work so that employees can produce maximum performance and provide motivation for employees to develop their careers. Keywords : employee performance, work motivation, career development